Responses of some ecophysiological traits of sessile oak (Quercus petraea) to drought stress and heat wave in growing season of 2003 - Mészáros, Ilona (Acta Biologica Szegediensis, 2008)
The effects of drought and heat wave appeared in growing season of 2003 on some physiological traits of Quercus petraea were studied at the Sikfôkút research site. There were comparative measurements in the subsequent humid growing season of 2004. Drought reduced significantly the leaf mass increment of Quercus petraea in the dry year (2003) which was reflected in lower SLM too as compared to 2004. Chlorophyll content showed inter-annual and within-canopy variability. Carotenoid content was 1,5-2 times larger in spring than in summer. In summer of 2003 VAZ pool was larger especially in sun leaves than in 2004. Values of Fv/Fm were lower in 2004 than 2003 which indicated lasting drought effects on the photochemical activity of leaves of sessile oak.